Factors Affecting Gastric Perforation Patient Outcome with History of Arthritis and Long Term Use of NSAIDs in Dr. Kariadi Semarang Period 2020 – 2022 - Nugroho, Leonardo Cahyo; Fauzi, Ardi; Priambodo, Agus (Medica Hospitalia : Journal of Clinical Medicine, 2023)
Background: The incidence of gastric perforation gives a high mortality outcome. The second most common cause of gastric perforation is long-term use of NSAIDs. In cases of arthritis during the COVID-19 pandemic, a conservative therapeutic approach and administration of NSAIDs are preferred. Due to this, researchers want to know the factors affecting gastric perforation cause by NSAIDs. Method: An analytic descriptive study with a retrospective cohort study design, using electronic medical records of patients at RSUP Dr. Kariadi Semarang from January 2020 - December 2022. Data collected was in the form of demographics, diagnoses, procedures, preoperative conditions, scoring system, and outcome. Results: PULP score, one of prognostic factor, has a good level of significance compared to other scoring systems in determining the prognostic mortality of patients with gastric perforation. The combination of variables between the type of NSAIDs and the type of arthritis has a direct correlation with a positive inter-variable power of 86.7% and a significance of 0.049 on patient outcome. Conclusion: NSAIDs pose a risk of gastric perforation in long-term use. tNSAIDs carry a higher risk inducing gastric perforation than selective NSAIDs.